PENGARUH METODE BERMAIN PUZZLE TERHADAP KEMAMPUAN SOSIALISASI ANAK RETARDASI MENTAL DI SLB C YAKUT PURWOKERTO - Rahmaya Nova Handayani (Viva Medika, 2012)
Child " special needs" or children with special needs , including children who experienceobstacles in development of behavior . The behavior of these children , which is comprisedof speech and occupational not develop as a normal child . Both types of behavior areessential for communication and socialization , so that when these obstacles are notaddressed quickly and appropriately , then the children's learning process will also behampered . One of the educational game is a puzzle game . Puzzles can provide anopportunity to learn a lot . One of the benefits of playing puzzle is to improve social skills.The aim in this study was to determine the effect of the method of playing puzzlesocialization skills of children with mental retardation in SLB C YAKUT Purwokerto.This study is a pre- experimental design while the study was non - randomized one-grouppre - post test design . The sampling technique using a random sampling of 30 children.Statistical test using the Wilcoxon Signed Rank Test of significance Î± = 0.05.The results showed the average value of the respondents' social skills before playingpuzzlesebesar 20.17 and after 114.0 . Statistical analysis showed that the therapy puzzleshave significant effects where p = 0.001 ( p < 0.05 ) . The conclusion from this researchthat puzzle play therapy effective against social skills in children with mental retardationin SLB C YAKUT Purwokerto. Keywords : puzzle , the ability of socialization , children with mental retardation